Controverses environnementales et arbitrages politiques : les logiques d’action du système Étang de Berre/Basse-Durance - Martin Laurenceau; François Molle (VertigO)
In 2027 EU member countries are expected to achieve good status or good potential of water bodies in the context of the 2000 Water Framework Directive (WFD), exacerbating tensions in some territories. Indeed, the achievement of good status is based on achieving trade-offs between multiple uses, leading to a new social and spatial distribution of costs and profits. We suggest that these arbitrations cannot be based only on criteria of ecological efficiency and economic costs, as proposed by the WFD, and must consider (i) the interdependencies between water bodies and associated uses, as well as (ii) the logics of action underpinning the scenarios promoted by the various actors involved. Based on the historical evolution of the étang de Berre and the lower-Durance River basin, we unpack the hydrological, ecological and socio-economic connections between these territories. Secondly, we highlight the problematisation and interessement processes that underlie each of the scenario brought up by the players involved, as well as their consequences in terms of the distribution of costs and benefits. Finally, we discuss the ability of the different, and partly incompatible, logics of action to prevail and to influence the future decision of the European Commission regarding the possible downward revision of the ecological objectives in the étang de Berre / lower-Durance system.